2008
DOI: 10.1111/j.1365-2923.2001.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of basic clinical skills training programmes: a cross-sectional comparison of four medical schools

Abstract: Objective Training in physical diagnostic skills is an important part of undergraduate medical education. The objective of this study was to study the outcome of skills training at four medical schools.Context At the time of the study, three schools had a traditional lecture-based curriculum and one school had a problem-based learning curriculum with a longitudinal skills training programme. All schools offer extended exposure to clerkships 1 1 .Method A cross-sectional study in four medical schools was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 16 publications
2
26
1
7
Order By: Relevance
“…Exposure to clinical environments Clinical skills in rural setting e437 does not by itself lead to improved clinical skills. Students may need a structured curriculum, with teaching and assessment in the skills they are expected to acquire (Culhane et al 1993;Remmen et al 2001;Stolarek 2007). However, equally an emphasis on self-learning supported by mentoring and or supervision may be strongly advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to clinical environments Clinical skills in rural setting e437 does not by itself lead to improved clinical skills. Students may need a structured curriculum, with teaching and assessment in the skills they are expected to acquire (Culhane et al 1993;Remmen et al 2001;Stolarek 2007). However, equally an emphasis on self-learning supported by mentoring and or supervision may be strongly advocated.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that clinical skills laboratory training at an early phase diminishes the anxiety of preclinical students' related to the core clinical skills and positively influences their learning during a clerkship [21,22]. In our study, while self-test directed students using stepwise processing strategies were moderately satisfied with the content, organization and planning of the clinical skills program, the students who lack regulation and using knowledge in mental models of learning were less satisfied with the content, organization and planning of the clinical skills program.…”
Section: Discussionmentioning
confidence: 99%
“…Also they were less satisfied about acquired knowledge and skills. Clinical skills training at early stages seem to offer the students a superior preparation resource for clerkships as well as influencing the students' learning abilities during the clerkships [22]. So preclinical students prepared to patient-physician relationships and physical examination and their competency related to cognitive and affective domains improved this.…”
Section: Discussionmentioning
confidence: 99%
“…This will help students to get formal procedural training maintained skills performance superiority over subsequent years of medical school [10]. Several studies showed that clinical skills curricula have demonstrated significant improvements in medical student confidence after implementation of formal procedural skills courses [9,11,12].…”
Section: Teaching Medical Proceduresmentioning
confidence: 99%